Authentification of person with dynamically entered signature using of normal ortogonal discrete transformation - Rybina, Irina; Nizhebetska, Yuliya (Видавництво Львівської політехніки, 2010)
In this paper the task of authentification of person with dynamically entered signature using normal transformation is solved. High reliability and sensitivity of this method are shown. The results can be used for creation information defence systems.
Keywords: authentification; normal transformation; the coefficient of transforms